2004
DOI: 10.2139/ssrn.624202
|View full text |Cite
|
Sign up to set email alerts
|

Finance Constraints and Inventory Investment: Empirical Tests with Panel Data

Abstract: The author empirically tests two aspects of the interaction between financial variables and inventory investment: negative cash flow and finance constraints due to asymmetric information. This is one of the first studies of inventory investment and finance constraints using Canadian data. A sample of Canadian manufacturing firms over the period 1992Q2-1999Q4 is split into subsamples based on age, bond rating, and size to reflect expected differences in degrees of asymmetric information problems. The findings a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…A negative and significant impact was recorded for inventory behavior which implied that companies respond in part by altering their level of inventories when there is an increase in borrowing costs. Cunningham (2004) in a study of 166 Canadian firms however obtained a different results from those obtained from the US, UK and Dutch firms. The study estimated three separate models consisting of old and young firms, bond-rated versus unrated firms, large versus small firms.…”
Section: Empirical Literaturementioning
confidence: 71%
See 1 more Smart Citation
“…A negative and significant impact was recorded for inventory behavior which implied that companies respond in part by altering their level of inventories when there is an increase in borrowing costs. Cunningham (2004) in a study of 166 Canadian firms however obtained a different results from those obtained from the US, UK and Dutch firms. The study estimated three separate models consisting of old and young firms, bond-rated versus unrated firms, large versus small firms.…”
Section: Empirical Literaturementioning
confidence: 71%
“…However, in another study using a panel data for US firms, Choi and Kim (2001) found that liquidity constraint impacted negatively on inventory investment. However, Cunningham (2004) in a study of Canadian firms did not observe any significant differences in the sensitivity of inventory investment to cash flow of firms with asymmetric information from those without. Moreover, Benito (2005) in a study of UK and Spanish firms came out with a finding that financial effects associated with liquidity and borrowing ratio were estimated to be stronger in UK firms considered to be market-based than Spanish firms which were classified as bank-based.…”
Section: Introductionmentioning
confidence: 82%
“…On the other hand, other studies use the foundation year of the firms (Arslan et al 2006;Bhaduri 2005;George et al 2011;Riaz et al 2016). In this study, firms are classified in each country based on their foundation year and defined as financially constrained or unconstrained, depending on whether their age is below or above the median age value (Cunningham, 2011;Guariglia & Mateut, 2010;Schiantarelli & Sembenelli, 2000).…”
Section: Agementioning
confidence: 99%
“…Bu çalışmada da sekiz gelişmekte olan ülkede (Arjantin, Brezilya, Şili, Yunanistan, Meksika, Polonya, Güney Afrika, Türkiye) yer alan 486 firmanın 2005-2018 yılları arasında nakit-nakit akışı duyarlılığı 2005-2018 yılları arasında analiz edilmiştir. Literatürle bağlantılı olarak firmalar büyüklük (Almeida ve diğerleri, 2004;Arslan ve diğerleri, 2006;Chang ve diğerleri, 2007;Crisóstomo ve diğerleri, 2014;Devereux & Schiantarelli, 1990;Gertler & Gilchrist, 1993, 1994Kadapakkam ve diğerleri, 1998); yaş (Arslan ve diğerleri, 2006;Bhaduri, 2005;Chen & Chen, 2012;Cunningham, 2011;Devereux & Schiantarelli, 1990;George ve diğerleri, 2011;Guariglia & Mateut, 2010;Riaz ve diğerleri, 2016); Kaplan ve Zingales Endeksi (Aǧca ve Mozumdar, 2008;Almeida ve diğerleri, 2004;Benligiray, 2017;Riaz ve diğerlerleri, 2016); Size ve Age Endeksi (SA1) (Aǧca & Mozumdar, 2008;Hadlock & Pierce, 2010;Machokoto ve diğerleri, 2019;Mulier ve diğerleri, 2016;Riaz ve diğerleri, 2016); Sales ve Age Endeksi (SA2) (Riaz ve diğerleri, 2016) yöntemlerine göre finansal açıdan kısıtlı ve kısıtlı olmayan firmalar şeklinde kategorize edilmiştir. Analiz sonuçlarına göre hem finansal açıdan kısıtlı hem de kısıtlı olmayan firmalarda nakit-nakit akışı duyarlılığı pozitif ve anlamlı bulunmuştur.…”
unclassified
“…Unlike previous studies, the coverage and size criterion does not reduce the impact of cash flow on inventory investment for financially constrained firms. Cunningham (2004) research about 166 publicly traded Canadian firms for the 1992-1994 period with the quarterly data. The classification schemes of firms are size, age and bond rating.…”
Section: Introductionmentioning
confidence: 99%